Evaluation of Serum parathyroid hormone level measurement in total thyroidectomy patients - MS, Islam; T, Sultana; D, Paul; AHMZ, Huq; S, Ferdoushi; AA, Chawdhury; MQ, Rahman; SU, Ahmed; ANN, Ahmed (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Postoperative hypoparathyroidism is a common complication after total thyroidectomy. It is necessary to diagnose hypoparathyroidism immediately after total thyroidectomy for minimizing complications. Objective: The objective of this study was to measure and to evaluate the serum parathyroid hormone level in total thyroidectomy patients. Methods: This prospective observational study was carried out in the Department of Clinical Pathology in collaboration with Department of Surgery & Department of Otolaryngology of BSMMU and Department of Otolaryngology of DMCH, Dhaka, during the period of September 2010 to August 2011. Results: Total 65 patients were studied irrespective of age and sex. Decreased serum PTH was found in 9 cases and normal parathyroid hormone was found in 56 cases. Male was 16.0% and female was 84.0%. Females were predominant. The incidence of hypoparathyroidism was 41.5%. Asymptomatic hypoparathyroidism was found in 8 and symptomatic hypoparathyroidism was found in 1 cases. Decreased serum PTH was developed mostly in malignant thyroid diseases. In relation to preoperative PTH values, intraoperative PTH levels were lower from 5.48% to 90.0%, (mean±SD in percentage is 65.3±16.7, p=.001) which is significant in paired t test. The mean difference of intraoperative (20 minutes after total thyroidectomy), parathyroid hormone levels were statistically significant (p<0.05) between patient with decreased parathyroid hormone and patient with normal parathyroid hormone in unpaired t-test. Conclusion: Serum parathyroid hormone level significantly decreased 20 minutes after total thyroidectomy. If clinical sign symptoms of hypoparathyroidism are not developed in postoperative period, patient is safe and can be discharged from hospital. Bangladesh J Otorhinolaryngol; April 2017; 23(1): 5-10